Implementation of digital marketing for UD Modern Y to expand website-based product marketing - Eko Muh Widodo; Afif Prasetyo; Rahendra Firman Sunartama; Cweto Bolodiko Ajarwiro; Almas Nurfarid Budi Prasetyo; Yantria Gusta Nugraha (Community Empowerment, 2023)
UD Modern Y is one of the SMEs in Mungkid District, Magelang Regency which is engaged in convection. In its development, the marketing method used is still conventional by utilizing word of mouth (WOM). This has resulted in the slow development of UD Modern Y and being unable to compete in the marketing of its products. Therefore the community service is carried out through digital marketing education by creating a website that can support many things, such as marketing, bookkeeping, and ordering. Digital Marketing in the form of a website is an important step in entering the world of e-commerce, with a website there will be a lot of potential in its development because the website is very flexible in its development. This program is carried out by developing a website followed by training and mentoring. At the end of the program, the UD Modern Y website was produced which can be accessed at https://udmodern.store and the management has been able to utilize the website as a new marketing medium to reach a wider market potential.